PENGGUNAAN TEKNOLOGI PENDIDIKAN DALAM PENGAJARAN DI SEKOLAH DASAR: TREN DAN DAMPAKNYA TERHADAP HASIL BELAJAR SISWA - Sarafiah Sarafiah; Abas Oya; Yuyun Yuningsih RS; Eva Nursa'ban (Pendikdas: Pendidikan Dasar, 2024)
This study aims to analyze and identify trends in the use of educational technology in teaching at the elementary school level from 2019 to 2024 and evaluate its impact on student learning outcomes. Using a bibliometric approach, data was collected from Crossref via the Publish or Perish application, focusing on keywords such as "educational technology," "elementary school teaching," "student learning outcomes," "interactive multimedia," and "e-learning." The analysis results indicate a significant increase in publications related to educational technology, with a peak occurring in 2022. The most cited articles, such as those by Anggraeni et al. (2021) and Rahmadani Taufina (2020), highlight the effective use of interactive multimedia and problem-based learning (PBL) models in enhancing student engagement and academic achievement. This research also identifies challenges faced by educators in integrating technology, including disparities in access and the need for ongoing training. The findings provide valuable insights for education practitioners and policymakers to better optimize the use of technology in the elementary education system. By recommending further research on new technologies and their impact on education, this study emphasizes that the utilization of educational technology is a crucial step in addressing the educational challenges in the digital era.